The Effects of Exposed Specific Facets and Sulfation on the Surface Acidity of Cu2O Solids. Issue 65 (23rd October 2019) - Wu, Yanan; Huang, Daofeng; Fu, Yingyi; Zhang, Li; Liu, Shixi; Tang, Gangfeng; Ren, Yuanhang; Ye, Lin; Chen, Xueying; Yue, Bin; He, Heyong
Abstract: Cuprous oxide microcrystals with 111, 111/100, and 100 exposed facets were synthesized. 31 P MAS NMR using trimethylphosphine as the probe molecule was employed to study the acidic properties of samples. It was found that the total acidic density of samples increases evidently after sulfation compared with the pristine cuprous oxide microcrystals. During sulfation, new 100 facets are formed at the expense of 111 facets and lead to the generation of two Lewis acid sites due to the different binding states of SO4 2− on 111 and 100 facets. Moreover, DFT calculation was used to illustrate the binding models of SO4 2− on 111 and 100 facets. Also, a Pechmann condensation reaction was applied to study the acidic catalytic activity of these samples. It was found that the sulfated 111 facet has better activity due to its higher Lewis acid density compared with the sulfated 100 facet. Abstract : Cuprous oxide microcrystals with 111, 111/100, and 100 exposed facets were synthesized. 31 P MAS NMR using trimethylphosphine as the probe molecule was employed to study the acidic properties of the samples. It was found that the models of SO4 2− bonded on Cu2 O and surface acidity of sulfated Cu2 O varies from different facets (see figure).